Preparation method of high-density lithium iron phosphate by step-by-step reduction coating, material and lithium battery
Patent Information
- Application Number
- CN202610860166.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-06-15
AI Technical Summary
当烧结温度低于800℃时,晶粒生长动力不足,难以获得满足高压实需求的大颗粒骨架;而若将温度提升至800℃以上,虽有助于晶粒长大,但会触发FeP、Fe2P、Fe3P等磷化铁杂质相的热力学成核与生长,这些副产物不仅不具备电化学活性,还会对电池的安全性能构成严重威胁
1.工艺窗口清晰可控:通过将还原成相与碳包覆分离,一次烧结专注于晶粒长大,二次烧结专注于包覆层构建,使得各阶段工艺参数均可独立优化,避免了传统一烧工艺中相互制约的矛盾,显著拓宽了高压实磷酸铁锂的制备工艺窗口;
Smart Images

Figure CN122393268B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery cathode material preparation technology, and in particular to a stepwise reduction coating preparation method, materials, and lithium batteries of high-pressure lithium iron phosphate. Background Technology
[0002] As energy storage systems rapidly evolve towards larger single-unit capacities, energy storage cells with capacities of 314Ah and above are gradually becoming the market mainstream. To reduce system integration costs and the levelized cost of electricity (LCOE) over the entire lifecycle, maximizing the amount of active material packed within the limited space of the cell casing has become an industry consensus. This trend directly drives the continuous increase in the compaction density of lithium iron phosphate cathode materials, which is now generally required to reach 2.60 g / cm³. 3 Above, and towards 2.70 g / cm 3 And move towards a higher level.
[0003] The key to achieving high compaction performance in lithium iron phosphate materials lies in constructing an optimized particle size distribution and reducing the specific surface area of the material. For mainstream lithium iron phosphate processes, this typically requires increasing the proportion of larger-diameter particles in the material and promoting the full growth and fusion of primary particles during sintering to balance processability with the stability of the pore structure after compaction. In traditional one-stage sintering processes, achieving these goals often requires increasing the sintering temperature to promote grain growth.
[0004] However, the traditional single-stage sintering process integrates raw material mixing, iron source reduction, lithium iron phosphate crystalline phase formation, and surface carbon coating into a single high-temperature heat treatment. While this process is concise and has high equipment utilization, it faces a series of irreconcilable contradictions within the high-temperature window required for producing high-compact products: First, there is a coexistence of limited grain growth and side reaction risks. The premature formation of the surface carbon coating layer during the heating process significantly inhibits the further growth and fusion of lithium iron phosphate grains. When the sintering temperature is below 800℃, the grain growth momentum is insufficient, making it difficult to obtain a large-particle framework that meets the high-compaction requirements. While raising the temperature above 800℃ helps grain growth, it triggers the thermodynamic nucleation and growth of iron phosphide impurity phases such as FeP, Fe2P, and Fe3P. These byproducts not only lack electrochemical activity but also pose a serious threat to the safety performance of the battery.
[0005] Second, the risk of increased iron deposition on the negative electrode is amplified. The iron phosphide secondary phase and its associated localized iron-rich regions are one of the main sources of iron ion dissolution during battery cycling. The dissolved iron ions migrate to the negative electrode surface and deposit, which may catalyze electrolyte decomposition, induce lithium dendrite growth, and in severe cases even lead to internal short circuits, causing irreversible damage to the long cycle life and intrinsic safety of the energy storage cell.
[0006] Third, the quality of the coating layer deteriorates. The intense carbothermic reduction reaction under high temperature conditions produces a large amount of gas, which can easily destroy the continuity and density of the carbon coating layer, thereby weakening the electronic conductivity network and interface stability of the material surface.
[0007] Therefore, how to synergistically achieve the large particle skeleton, low iron phosphate impurity phase content, and uniform and stable carbon coating layer required for high compaction in the same material system has become a key technical problem that urgently needs to be solved in the field of high-end lithium iron phosphate material manufacturing. Summary of the Invention
[0008] This invention aims to overcome the aforementioned defects in the traditional one-time sintering process for preparing high-density lithium iron phosphate materials, and provides a stepwise reduction-coating method for preparing high-density lithium iron phosphate. This method completes the reduction and grain growth functions, as well as the carbon coating function, in two separate heat treatment processes, thereby achieving precise control over each process stage. While maintaining high density and excellent electrochemical performance, it significantly reduces the risk of iron deposition on the anode.
[0009] To achieve the above-mentioned objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a stepwise reduction and coating preparation method for high-pressure lithium iron phosphate, comprising the following steps: (1) A slurry is prepared by mixing lithium source, anhydrous iron phosphate and first carbon source according to the molar ratio of lithium, iron and phosphorus elements of 1.01 to 1.03:1:1; (2) Grind and spray dry the slurry to obtain a primary sintering precursor; (3) The precursor of the first sintering is sintered at 730-795°C to reduce Fe3 to form lithium iron phosphate intermediate, and the total carbon content of the lithium iron phosphate intermediate after the first sintering is controlled to be 0.001-0.01wt%, so that a discontinuous and incomplete first carbon coating layer is formed on the surface of the lithium iron phosphate intermediate particles. (4) The lithium iron phosphate intermediate is naturally cooled to room temperature under nitrogen and inert gas, and is not pulverized, but is selectively sieved to eliminate large agglomerates. (5) Add a second carbon source to the cooled lithium iron phosphate intermediate and mix again; (6) The remixed material is sintered a second time at a temperature 10 to 180°C lower than the first sintering temperature to form a second carbon coating layer on the particle surface. (7) The material after secondary sintering is crushed, iron removed, sieved and mixed to obtain lithium iron phosphate material with high compaction and low negative electrode iron deposition. The molar ratio of carbon atoms provided by the first carbon source to iron atoms in ferric phosphate is 0.25 to 0.5:1; the molar ratio of carbon atoms provided by the second carbon source to iron atoms in ferric phosphate is 0.05 to 0.3:1.
[0010] In the preparation method of this invention, the entire heat treatment process is divided into two stages: primary sintering and secondary sintering. Primary sintering is carried out at a relatively high temperature, where the amount of the first carbon source added is precisely controlled. Its main function is to provide the atmospheric conditions required for reduction, promoting the full reduction of ferric iron in anhydrous iron phosphate and completing the formation of the lithium iron phosphate crystalline phase. Due to the small amount of the first carbon source, only an extremely thin and discontinuous first carbon coating layer forms on the particle surface after primary sintering, and the total carbon content of the material is strictly limited to below 0.1 wt%. This low residual carbon state is conducive to the free growth of grains and moderate sintering between particles during primary sintering, forming a dense large-particle framework structure, laying the foundation for subsequent high compaction.
[0011] After the first sintering, the material is cooled to room temperature under a protective atmosphere to avoid excessive reduction or abnormal grain growth at high temperatures. A second carbon source is then introduced for secondary coating, and a second sintering is performed at a temperature significantly lower than the first sintering temperature. This lower second sintering temperature prevents the particle skeleton from undergoing further changes at high temperatures, thus protecting the already formed dense structure. Furthermore, the second carbon source undergoes decomposition and carbonization under relatively mild conditions, resulting in a continuous and complete second carbon coating layer that is uniformly deposited on the surface of the particles formed in the first sintering, giving the material excellent electrical conductivity. The synergistic effect of the distribution of the two carbon sources and the temperature difference between the two sintering processes allows the final material to possess both the high-compaction characteristics of a large particle skeleton and the high conductivity of a continuous carbon coating layer. Since the reduction reaction is completed in the first sintering, the second sintering involves almost no change in the iron valence state, effectively avoiding the generation and migration of iron impurities, thereby controlling the iron deposition in the negative electrode to below 50 ppm.
[0012] It should be noted that the amount of iron deposited on the negative electrode is a direct indicator of the amount of iron ions dissolved and migrated to the negative electrode side in lithium iron phosphate materials. The lower the value, the lower the risk of iron dissolution in the material. In this application, "anode iron deposition amount" is used as a direct characterization value of the degree of iron dissolution. The anode iron deposition amount mentioned in this application refers to the value measured using the method defined in the "Performance Testing Methods and Evaluation Indicators" section of this application.
[0013] Preferably, the first carbon source is selected from one or more of glucose, sucrose, starch, citric acid, soluble starch, and polyethylene glycol. This carbon content range provides a sufficiently reducing atmosphere for the reduction of ferric phosphate while ensuring extremely low residual carbon content after a single sintering, thus not significantly hindering grain growth.
[0014] Preferably, the total carbon content of the material after secondary sintering is 0.35wt% to 1.40wt%; the second carbon source is selected from one or more of sucrose, glucose syrup, phenolic resin, asphalt, polyacrylonitrile, carboxymethyl cellulose, and polyvinyl alcohol. The second carbon source is often a carbon precursor with a high residual carbon content or good film-forming properties, in order to form a uniform and dense coating layer at a lower temperature.
[0015] Preferably, the solid content of the slurry in step (1) is 45wt% to 70wt%, and the D50 of the slurry after grinding is 0.3 to 1.5μm. Suitable solid content and particle size distribution are beneficial for obtaining precursor particles with good sphericity and good flowability through spray drying, and ensure uniform element diffusion during subsequent sintering.
[0016] Preferably, the holding time for the first sintering in step (3) is 4 to 16 hours, the sintering atmosphere is a nitrogen protective atmosphere or an inert atmosphere, and no additional strong reducing combustible gas is introduced. The reduction of ferric iron can be completed by relying on the reducing atmosphere generated by the self-decomposition of the first carbon source, without the need to introduce additional strong reducing gases such as hydrogen or carbon monoxide, which simplifies the process and improves safety.
[0017] Preferably, after cooling to room temperature in step (4), the material is sieved using a vibrating screen with an aperture of 2mm to 5mm to eliminate large agglomerates. Sieving prevents large agglomerates from entering the secondary mixing process, ensuring uniform mixing of the second carbon source.
[0018] Preferably, the re-mixing in step (5) is performed by dry mixing or atomized liquid mixing; when atomized liquid mixing is used, a drying step is also included after mixing, wherein the drying is performed by vacuum drying. Dry mixing is simple to operate, while atomized liquid mixing helps the second carbon source to spread evenly on the particle surface.
[0019] Preferably, the secondary sintering temperature in step (6) is 600–760°C, and the holding time is 2–10 h. The secondary sintering temperature is significantly lower than the primary sintering temperature, and the holding time is shorter, in order to avoid destructive sintering of the particle skeleton.
[0020] Secondly, this invention provides a lithium iron phosphate material, prepared by the stepwise reduction coating method of high-compact lithium iron phosphate as described in any of the preceding claims. This lithium iron phosphate material has a composite structure of a large-particle framework and a continuous carbon coating layer on the surface, with a powder compaction density ≥2.60 g / cm³. The large-particle framework is composed of tightly packed primary particles formed by a single sintering process, imparting high compressive strength and high-compacting performance to the material; the continuous carbon coating layer is formed by a second carbon source introduced through a secondary sintering process, uniformly coating the surface of the large particles to ensure unobstructed electron transport channels. The combination of these two elements enables the material to maintain good rate capability and cycling performance even under high-compacting conditions.
[0021] Thirdly, the present invention provides a lithium-ion battery comprising a positive electrode and a negative electrode, wherein the positive electrode comprises the aforementioned lithium iron phosphate material, and the iron deposition content of the negative electrode is ≤50ppm. This lithium battery, while ensuring high volumetric energy density, exhibits excellent interface stability at the negative electrode and a long cycle life.
[0022] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are: 1. Clear and controllable process window: By separating the reduction phase formation from the carbon coating, the first sintering focuses on grain growth, and the second sintering focuses on coating layer construction. This allows the process parameters at each stage to be optimized independently, avoiding the contradictions of mutual constraints in the traditional one-sintering process and significantly broadening the preparation process window of high-pressure lithium iron phosphate. 2. Side reactions are effectively suppressed: Only a small amount of the first carbon source is used in the first sintering stage, which avoids the generation of a strong reducing atmosphere at high temperature. The probability of the formation of iron phosphide impurities such as FeP, Fe2P, and Fe3P is significantly reduced from a thermodynamic and kinetic perspective, which fundamentally reduces the risk of intrinsic negative electrode iron deposition in the material and improves the long-term safety and reliability of the battery. 3. Balancing High Compaction and High Volume: Because there is no continuous carbon layer restricting surface diffusion during the single-stage sintering process, primary particles can fully grow and form a large particle skeleton within a relatively suitable temperature range of 730–795℃, avoiding the risks associated with using excessively high temperatures to achieve high compaction. The resulting material achieves a stable compaction density of 2.60 g / cm³. 3 The above can meet the design requirements of large-capacity energy storage cells; 4. Superior Conductive Network and Interface Stability: Secondary sintering is completed at a lower temperature, effectively protecting the integrity of the primary particle skeleton, while forming a more continuous and uniform conductive carbon coating layer than the primary sintering process. This structure not only improves the electronic conductivity and rate performance of the material, but also enhances the interfacial stability between the particle surface and the electrolyte, thereby improving the cycle life of the battery; 5. High industrial compatibility: The method and steps of this invention are clear and highly compatible with existing continuous production lines for iron phosphate and mainstream sintering equipment (such as roller furnaces and pusher furnaces). It does not require disruptive modifications to existing production equipment and has a good industrialization foundation and prospects for large-scale application. Attached Figure Description
[0023] Figure 1 A transmission electron microscope image of the primary sintering intermediate prepared in Example 1 of this invention; Figure 2 A transmission electron microscope image of the lithium iron phosphate material prepared in Example 1 of this invention; Figure 3 This is a comparison diagram of the powder compaction density of the lithium iron phosphate material prepared in Example 1 of the present invention and the material in Comparative Example 1; Figure 4 The image shows an X-ray diffraction (XRD) pattern, in which... Figure 4 (a) is the X-ray diffraction (XRD) pattern of the lithium iron phosphate material prepared in Example 1 of the present invention; Figure 4 (b) is the X-ray diffraction (XRD) pattern of the material in Comparative Example 1; Figure 5 The image shows the cycle performance curve of a lithium battery assembled from the lithium iron phosphate material prepared in Example 1 of this invention. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the embodiments of this invention will be described in detail below. However, those skilled in the art should understand that the listed embodiments are only for explaining and illustrating this invention and do not constitute a limitation on the scope of protection of this invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.
[0025] Unless otherwise specified, the raw materials and equipment used in the following examples and comparative examples are all commercially available products in the art. For ease of process comparison, each example and comparative example assumes a molar amount of ferric phosphate of 100 moles as the basis for material input calculations.
[0026] Example 1 (1) Lithium carbonate, anhydrous iron phosphate and glucose as the first carbon source are mixed according to the molar ratio of lithium, iron and phosphorus elements of 1.01:1:1. The molar ratio of carbon atoms provided by glucose to iron atoms in iron phosphate is 0.4:1. Pure water is added to prepare a slurry with a solid content of 58wt%.
[0027] (2) The obtained slurry is transferred to a sand mill for grinding until the median particle size D50 of the particles in the slurry reaches 0.8 μm. Then, it is spray dried and granulated to obtain a primary sintering precursor powder.
[0028] (3) The precursor for primary sintering is placed in a sintering furnace under nitrogen atmosphere protection and sintered at 770°C for 8 hours. During this process, trivalent Fe is reduced to divalent Fe and olivine-type lithium iron phosphate crystals are generated. The total carbon content of the intermediate obtained after primary sintering is about 0.01 wt%, and a first carbon coating layer is formed on the particle surface. The first carbon coating layer is discontinuous, incomplete, or extremely thin. Because the carbon content of the first carbon coating layer is <0.1 wt%, it appears as a discontinuous island distribution or an extremely thin layer with a thickness of less than 1 nanometer on the particle surface. It cannot effectively hinder the migration of matter during the grain growth process. This is fundamentally different from the continuous carbon coating layer used in the traditional sense to improve conductivity. Usually, the carbon content of the continuous carbon coating layer is >0.5 wt%.
[0029] (4) The lithium iron phosphate intermediate after one sintering is naturally cooled to room temperature in the furnace under a nitrogen protective atmosphere. After cooling, it is not subjected to air jet milling, mechanical milling or roller crushing, but simply sieved through a vibrating screen with a 2mm aperture to eliminate large agglomerates. This treatment does not change the median particle size D50 and particle morphology.
[0030] (5) Add phenolic resin as a second carbon source to the cooled lithium iron phosphate intermediate. The molar ratio of carbon atoms provided by the phenolic resin to iron atoms in the iron phosphate is 0.15:1. Then, use a dry high-speed mixer to mix again so that the second carbon source is uniformly dispersed on the surface of the intermediate particles.
[0031] (6) The remixed material is transferred to a sintering furnace and sintered again at 680°C for 5 hours. During this process, the phenolic resin undergoes pyrolysis and carbonization, forming a uniform and continuous carbon coating layer on the surface of the lithium iron phosphate particles.
[0032] (7) The material after secondary sintering is subjected to conventional airflow pulverization, electromagnetic iron removal, sieving and classification and batch mixing to finally obtain high-pressure lithium iron phosphate cathode material.
[0033] Example 2 The difference from Example 1 is as follows: (1) The primary carbon source is sucrose, and the solid content of the slurry is 62 wt%. (2) The medium-sized particles were ground to a median particle size D50 of 0.6 μm; (3) The first sintering temperature was 785℃, the holding time was 6h, and the total carbon content of the intermediate was 0.003wt%. (5) The second carbon source is polyethylene glycol, with a carbon atom to iron molar ratio of 0.15:1, and is mixed by dry method; (6) The secondary sintering temperature is 700℃ and the holding time is 4h.
[0034] The remaining steps are the same as in Example 1.
[0035] Example 3 The difference from Example 1 is as follows: (1) The molar ratio of lithium, iron and phosphorus is 1.03:1:1, the primary carbon source is starch, and the solid content of the slurry is 55 wt%. (2) The medium-sized particles were ground to a median particle size D50 of 0.7 μm; (3) The first sintering temperature is 750℃, the holding time is 10h, and the total carbon content of the obtained intermediate is about 0.01wt%; (5) The second carbon source is sucrose, and the molar ratio of carbon atoms to iron is 0.18:1. It is sprayed onto the surface of intermediate particles by aqueous solution atomization spraying, and then vacuum dried. (6) The secondary sintering temperature is 650℃ and the holding time is 6h.
[0036] The remaining steps are the same as in Example 1.
[0037] Comparative Example 1 (Traditional single-firing process, high temperature) This comparative example uses the same formulation as Example 1, but all carbon sources (the amount of carbon corresponding to glucose and phenolic resin) are added at once in step (1), i.e., the molar ratio of carbon atoms provided by the total carbon source to iron atoms in ferric phosphate is 0.55:1. Steps (4) to (6) are omitted, and the precursor is directly sintered at 810°C for 8 hours. Subsequent processing is the same as step (7) of Example 1.
[0038] Comparative Example 2 (Traditional single-firing process, low temperature) This comparative example follows the same feeding method as Comparative Example 1, except that the primary sintering temperature is reduced to 760℃ while the holding time remains unchanged at 8 hours.
[0039] Table 1 Summary of main process parameters for examples and comparative examples
[0040] Table 2 Summary of Material Performance Test Results for Examples and Comparative Examples
[0041] Performance testing methods and evaluation metrics 1. Carbon content: Detected using a high-frequency infrared carbon-sulfur analyzer.
[0042] 2. Compacted density: The test was conducted in accordance with the national standard GB / T44330-2024 "Determination of compacted density of lithium-ion battery cathode material powder".
[0043] 3. Median particle size (D50): Detected using a Malvern Laser Particle Size Analyzer 3000.
[0044] 4. Iron deposition amount and cycle retention rate at the negative electrode: Battery fabrication: The obtained lithium iron phosphate positive electrode material, conductive agent Super-P, and binder PVDF were mixed at a mass ratio of 95:2.5:2.5. An appropriate amount of N-methylpyrrolidone (NMP) was added to form a slurry, which was then coated onto aluminum foil. After drying, rolling, and slitting, the slurry was formed into positive electrode sheets. Graphite was used as the negative electrode, with an N / P ratio of 1.08. The electrolyte consisted of 1 mol / L LiPF6 dissolved in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 1:1:1. Button cells or pouch cells were assembled for testing.
[0045] Cycle retention: The cycle retention is calculated by performing 500 charge-discharge cycles at 1C within a voltage range of 2.5V to 3.65V at 45°C. The percentage obtained by dividing the discharge capacity of the 500th cycle by the discharge capacity of the 1st cycle is the cycle retention rate.
[0046] Negative Electrode Iron Deposition Test: After the cycle test, the battery was charged to 3.65V using a 0.2C current, and then charged at a constant voltage until the current was less than or equal to 0.05C. The battery was disassembled in an argon glove box with water and oxygen contents both less than or equal to 1ppm. The negative electrode sheet was removed and thoroughly cleaned with ethyl methyl carbonate (EMC) to remove any residual electrolyte. Nine points were evenly selected on the cleaned negative electrode sheet for sampling. Based on the dry weight of the negative electrode powder, the iron content was measured using inductively coupled plasma optical emission spectrometry (ICP-OES). The average value of the nine points was taken as the final negative electrode iron deposition amount. This value directly reflects the degree of iron ion dissolution in the lithium iron phosphate material. The lower the negative electrode iron deposition amount, the lower the risk of iron dissolution in the material.
[0047] Results Analysis A comparison of Table 1 and Table 2 shows that: 1. Compacted density and particle size: In Examples 1-3 of this invention, through a stepwise sintering process, sufficient particle growth was achieved in the first sintering stage. The final products all had a D50 greater than 0.9 μm and a compacted density greater than 2.66 g / cm³. 3 Although Comparative Example 2 was also sintered at 760℃, the premature formation of the carbon layer due to the addition of all the carbon source hindered particle growth, resulting in a D50 of only 0.71 μm and the lowest compaction density (2.55 g / cm³). 3 This indicates that stepwise sintering can effectively resolve the contradiction between grain growth and carbon coating.
[0048] 2. Anode Iron Deposition Amount: This is one of the most significant technical effects of this invention. The anode iron deposition amounts in the embodiments are all at extremely low levels of 31 ppm or below. In contrast, Comparative Example 1, due to the use of high-temperature (810°C) single-pass sintering, resulted in the formation of a large amount of iron phosphide secondary phase, and its anode iron deposition amount reached as high as 330 ppm, more than ten times that of the embodiments. This fully demonstrates the significant advantages of the method of this invention in suppressing side reactions and improving the intrinsic safety and lifespan of materials.
[0049] 3. Overall electrochemical performance: The examples maintained high compaction density while also exhibiting excellent cycle retention (all not less than 94.7%). Comparative Example 1, although having a reasonable compaction density, showed significantly deteriorated cycle stability due to severe iron deposition on the negative electrode.
[0050] 4. By Figure 1 It can be seen that the intermediate obtained after one sintering in Example 1 does not have a carbon layer on its surface, confirming that a continuous carbon coating has not formed on the surface; Figure 2 It can be seen that after the second firing, the lithium iron phosphate material in Example 1 was coated with a uniform and continuous carbon layer; from Figure 3 It can be seen that under a pressure of 221.53 MPa (3T), the compacted densities of Example 1 and Comparative Example 1 are 2.68 g / cm³. 3 and 2.65g / cm 3 ;Depend on Figure 4 (a) and Figure 4 (b) It can be seen that the characteristic peaks of XRD in Example 1 and Comparative Example 1 correspond to the standard card of lithium iron phosphate, with no impurities, confirming the synthesis of pure-phase lithium iron phosphate. No carbon peaks were found, indicating that the surface carbon is amorphous. The peaks in Example 1 are sharper than those in Comparative Example 1, indicating that the material obtained in Example 1 has larger grains. Figure 5 It can be seen that the battery made from the lithium iron phosphate material obtained in Example 1 has a specific capacity of 319.34 Ah in the first cycle and a capacity of 303.06 Ah in the 500th cycle, with a capacity retention rate of 94.90%.
[0051] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art can make various improvements and modifications without departing from the technical principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A stepwise reduction-coating preparation method for high-pressure lithium iron phosphate, characterized in that, Includes the following steps: (1) A slurry is prepared by mixing lithium source, anhydrous iron phosphate and first carbon source according to the molar ratio of lithium, iron and phosphorus elements of 1.01 to 1.03:1:1; (2) Grind and spray dry the slurry to obtain a primary sintering precursor; (3) The precursor of the first sintering is sintered at 730-795°C to reduce Fe3 to form lithium iron phosphate intermediate, and the total carbon content of the lithium iron phosphate intermediate after the first sintering is controlled to be 0.001-0.01wt%, so that a discontinuous and incomplete first carbon coating layer is formed on the surface of the lithium iron phosphate intermediate particles. (4) The lithium iron phosphate intermediate is naturally cooled to room temperature under nitrogen and inert gas, and is not crushed, but only sieved to eliminate large agglomerates; (5) Add a second carbon source to the cooled lithium iron phosphate intermediate and mix again; (6) The remixed material is sintered a second time at a temperature 10 to 180°C lower than the first sintering temperature to form a second carbon coating layer on the particle surface. (7) The material after secondary sintering is crushed, iron removed, sieved and mixed to obtain lithium iron phosphate material with high compaction and low negative electrode iron deposition. The molar ratio of carbon atoms provided by the first carbon source to iron atoms in ferric phosphate is 0.25–0.5:1; the molar ratio of carbon atoms provided by the second carbon source to iron atoms in ferric phosphate is 0.05–0.3:
1. The lithium iron phosphate material has a composite structure of a large particle skeleton and a continuous carbon coating layer on the surface, and the powder compaction density is ≥2.60 g / cm³. 3 .
2. The stepwise reduction and coating preparation method of high-pressure lithium iron phosphate according to claim 1, characterized in that, The first carbon source is selected from one or more of glucose, sucrose, starch, citric acid, soluble starch, and polyethylene glycol.
3. The stepwise reduction and coating preparation method of high-pressure lithium iron phosphate according to claim 1, characterized in that, The total carbon content of the material after secondary sintering is 0.35wt% to 1.40wt%; the second carbon source is selected from one or more of sucrose, glucose syrup, phenolic resin, asphalt, polyacrylonitrile, carboxymethyl cellulose, and polyvinyl alcohol.
4. The stepwise reduction and coating preparation method of high-pressure lithium iron phosphate according to claim 1, characterized in that, In step (1), the slurry solid content is 45wt% to 70wt%, and the D50 of the slurry after grinding is 0.3 to 1.5μm.
5. The stepwise reduction and coating preparation method of high-pressure lithium iron phosphate according to claim 1, characterized in that, In step (3), the holding time for sintering is 4 to 16 hours, the sintering atmosphere is a nitrogen protective atmosphere and an inert atmosphere, and no additional strong reducing combustible gas is introduced.
6. The stepwise reduction and coating preparation method of high-pressure lithium iron phosphate according to claim 1, characterized in that, After cooling to room temperature in step (4), the material is sieved using a vibrating screen with an aperture of 2mm to 5mm to eliminate large agglomerates.
7. The stepwise reduction and coating preparation method of high-pressure lithium iron phosphate according to claim 1, characterized in that, The re-mixing in step (5) is carried out by dry mixing or atomized liquid mixing; when atomized liquid mixing is used, a drying step is also included after mixing, and the drying is carried out by vacuum drying.
8. The stepwise reduction and coating preparation method of high-pressure lithium iron phosphate according to claim 1, characterized in that, In step (6), the temperature for the second sintering is 600-760℃, and the holding time is 2-10h.
9. A lithium iron phosphate material, characterized in that, The lithium iron phosphate material is prepared by the stepwise reduction coating method of high-pressure lithium iron phosphate according to any one of claims 1 to 8, wherein the lithium iron phosphate material has a composite structure of a large particle skeleton and a continuous carbon coating layer on the surface, and the powder compaction density is ≥2.60 g / cm³. 3 .
10. A lithium battery, characterized in that, The battery includes a positive electrode and a negative electrode, wherein the positive electrode comprises the lithium iron phosphate material as described in claim 9, and the iron deposition amount of the negative electrode is ≤50ppm.
Citation Information
Patent Citations
Method for prolonging cycle life of lithium iron phosphate material
CN118270751A
Method for preparing lithium iron manganese phosphate positive electrode material from lithium iron phosphate waste material
CN120987288A